2008
DOI: 10.1099/vir.0.83331-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residues in the receptor-binding domain (RBD) of the spike protein of human coronavirus NL63 that are critical for the RBD–ACE2 receptor interaction

Abstract: Human coronavirus NL63 (NL63), a member of the group I coronaviruses, may cause acute respiratory diseases in young children and immunocompromised adults. Like severe acute respiratory syndrome coronavirus (SARS-CoV), NL63 also employs the human angiotensinconverting enzyme 2 (hACE2) receptor for cellular entry. To identify residues in the spike protein of NL63 that are important for hACE2 binding, this study first generated a series of S1-truncated variants, examined their associations with the hACE2 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 40 publications
4
84
0
2
Order By: Relevance
“…However, this study demonstrated that the role of ACE-2 residue 353 was noticeably different. Substitution of the resident lysine for alanine reduced, but did not abolish, SARS-CoV S binding, while it effectively abolished binding by NL63 S. In addition, as the end points in our constructs differed somewhat from those published by Li et al (2007), our data reduced the carboxy-terminal boundary of the NL63 S RBD in an analogous Fc-fusion protein configuration from residue 749 to 739; however, this boundary is not reduced as far as residue 616 as recently described by Lin et al (2008). An affinity of interaction with ACE-2 by NL63 S of 10–100-fold less than that of SARS-CoV S would explain our inability to obtain a sound K d for the interaction by surface plasmon resonance.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…However, this study demonstrated that the role of ACE-2 residue 353 was noticeably different. Substitution of the resident lysine for alanine reduced, but did not abolish, SARS-CoV S binding, while it effectively abolished binding by NL63 S. In addition, as the end points in our constructs differed somewhat from those published by Li et al (2007), our data reduced the carboxy-terminal boundary of the NL63 S RBD in an analogous Fc-fusion protein configuration from residue 749 to 739; however, this boundary is not reduced as far as residue 616 as recently described by Lin et al (2008). An affinity of interaction with ACE-2 by NL63 S of 10–100-fold less than that of SARS-CoV S would explain our inability to obtain a sound K d for the interaction by surface plasmon resonance.…”
supporting
confidence: 60%
“…However, while confirming that full-length SARS-CoV S appeared to bind to ACE-2-expressing cells more efficiently than NL63 S, the SARS-CoV RBD was less efficient at competing with NL63-mediated pseudotype entry than competition with SARS-CoV-mediated entry (IC 50 of ∼200 ng ml −1 for NL63 compared with ∼50 ng ml −1 for SARS-CoV) (Li et al , 2007). A recent report suggests that the minimum NL63 RBD lies between residues 476 and 616 and that, expressed alone, the binding affinity with ACE-2 reaches that observed for SARS-CoV S (Lin et al , 2008). Here, using a wholly recombinant system that precludes the involvement of any other cell surface factor present on mammalian cells, such as lectins [e.g.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…One may assume that such binding will result in the efficient inactivation of the virus. Unfortunately, it was not possible to determine whether HTCC polymer hampers NL63-S/ACE2 interaction, as the affinity of NL63-S to ACE2 is very low (Lin et al, 2008;Mathewson et al, 2008) and it was not possible to visualize this process with accessible methods. Careful analysis of polymers suggests that the combination of particular polymeric chain and its proper substituent is indispensable for its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the virus is not well studied at a molecular level with only the spike (Lin et al, 2008(Lin et al, , 2011Mathewson et al, 2008) and ORF3 proteins (Fielding and Suliman, 2009;Muller et al, 2010) previously characterized. In this work, the HCoV-NL63 N was expressed in mammalian and bacterial systems.…”
Section: Introductionmentioning
confidence: 99%